(untitled) (Scientific journal of the Fergana State University, 2025)
The article analyzes the fact that the issue of personal spirituality plays an important role in various religions, in particular in Islamic teachings, and that due to independence, studying it from the perspective of Islamic teachings and its values remains relevant. In Islam, the concept of "knowledge" has a broad meaning. When it comes to knowledge, knowledge is defined as a value, and not only religious views and religious knowledge are meant. It is analyzed that knowledge is considered in a broad sense as a factor that determines the level of a person’s entire spirituality, attitude to life, and living.